‘A Comparison of the Contents of the Codes of Ethics of Canada’s Largest Corporations in 1992 and 2003’ - Singh, Jang B. (Journal of business ethics, 2006)
This paper compares the findings of content analyses of the corporate codes of ethics of Canada’s largest corporations in 1992 and 2003. For both years, a modified version of a technique used in several other studies was used to determine and categorize the contents of the codes. It was found, inter alia, that, in 2003, as in 1992, more of the codes were concerned with conduct against the firm than with conduct on behalf of the firm. Among the changes from 1992 to 2003 were a significant increase in the frequency of mention of environmental affairs, legal responsibility as the basis of codes and enforcement/compliance procedures.